IMPLEMENTASI NILAI PENDIDIKAN AGAMA HINDU DALAM PROGRAM 7 KEBIASAAN ANAK INDONESIA HEBAT DI SMP NEGERI 1 KERAMBITAN KABUPATEN TABANAN - I Gede Made Boga Asta Wiguna; I Nyoman Alit Supandi; Kadek Dwi Sentana Putra (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2026)
This study aims to analyze the implementation of Hindu Religious Education values in the 7 Habits of Great Indonesian Children Program at SMP Negeri 1 Kerambitan. The study was motivated by the importance of strengthening students’ character education through positive habituation amid technological developments and social changes. The program includes waking up early, worshipping, exercising, eating healthy and nutritious food, loving learning, socializing, and sleeping early. Hindu Religious Education values such as Sraddha and Bhakti, Susila, Tat Twam Asi, Tri Hita Karana, Ahara, and Yoga were implemented to develop students who are religious, disciplined, healthy, and responsible. This study employed a qualitative approach with a phenomenological research design. Data were collected through observation, interviews, documentation, and literature study. The informants consisted of the principal, Hindu Religious Education teachers, homeroom teachers, and students. Data analysis used the Miles and Huberman interactive model, including data reduction, data presentation, and conclusion drawing. The findings showed that the implementation of Hindu Religious Education values in the program was carried out systematically and continuously through habituation activities at school. Supporting factors included teacher role models, a religious school culture, principal support, parental involvement, and adequate facilities. The program positively impacted students’ character development, particularly in discipline, religiosity, responsibility, social awareness, and healthy lifestyles.